Obi, gerbil on a mission! - Delaney, M. C. (Michael Clark) (Dial Books for Young Readers, 2012)
When pet gerbil Obi's owner Rachel gets a new puppy, Obi is jealous, but when the puppy runs away it is up to Obi to brave the dangers of the outside world and bring the new pet home.